The return of large numbers to the battlefield: quantitative implications of the Ukraine War on China’s ambitions for Taiwan (Journal of the Spanish Institute for Strategic Studies, 2025)
The Ukraine War has highlighted the importance of numbers in military conflicts between superpowers, demonstrating that these wars still largely adhere to modern-era parameters and the massive use of conventional weapons. It is inevitable to question how these observations influence the case of China’s ambitions over Taiwan, which could be the most dangerous source of tensions the world faces. China has a very large numerical base, which is the focus of this research, that strengthens its position and could potentially result decisive on the geopolitical board. Observing the Ukraine War calls for caution and emphasizes the importance of not relying solely on the deterrence of US military superiority to maintain the status quo regarding Taiwan. Additionally, it underscores the need for the West to promote policies that strengthen its defense industrial bases.
Keywords: Defense; Military; Conflict; China; Geopolitics